2019
DOI: 10.1016/j.applanim.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Classification of ingestive-related cow behaviours using RumiWatch halter and neck-mounted accelerometers

Abstract: Highlights Simple decision-tree (DT) algorithm to classify feeding and ruminating behaviours  The DT performs similar to support vector machine and a RumiWatch noseband. The use of a simple DT would help implementing the algorithm on the on-cow sensor  It would enable online measurements of the ingestive-related cow behaviours Abstract A new simple decision-tree (DT) algorithm was developed using the data from a neck-mounted accelerometer for real-time classification of feeding and ruminating behaviours of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 40 publications
0
36
1
1
Order By: Relevance
“…Studies on cattle behavior have indicated that illness causes animals to spend less time feeding and more time resting [ 43 ]. Feeding and ruminating behavior in cattle provides significant information about their productivity, health, and welfare [ 44 ]. Changes in ruminating and feeding timing of cows are indicative of an underlying alteration in their welfare and comfort [ 45 ].…”
Section: Assessing Adaptation Physiology Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on cattle behavior have indicated that illness causes animals to spend less time feeding and more time resting [ 43 ]. Feeding and ruminating behavior in cattle provides significant information about their productivity, health, and welfare [ 44 ]. Changes in ruminating and feeding timing of cows are indicative of an underlying alteration in their welfare and comfort [ 45 ].…”
Section: Assessing Adaptation Physiology Parametersmentioning
confidence: 99%
“…Wearable accelerometers have been evaluated as a tool for measuring cow behavior [ 44 ]. HOBO accelerometers, which are attached to the jaws of cows, can record the time each animal spends grazing and ruminating [ 47 ].…”
Section: Assessing Adaptation Physiology Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Vá zquez-Diosdado [6] designed a mixed multi-level model to automatically detect the drinking behavior of dairy cows, with environmental temperature, parity, and average monthly milk production as variables. Benaissa [7] installed accelerometers on cows to identify their feeding, rumination, and other digestive activities and classifying the behaviors with a DT model. By installing an inertial measurement unit on the backs of cows, Achour [8] monitored the standing, lying on the side, and walking behaviors of cows.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the main focus was put on gait parameters-step overlap, hoof release angle and back arch curvature [5][6][7]. Raw data of Benaissa et al (2019) [8]. illustrate that the widely used collar-mounted accelerometer classifies ruminating and feeding behaviors with accuracy closely comparable to the RumiWatch noseband sensor [8].…”
Section: Introductionmentioning
confidence: 99%